Kiril Popoff - a pioneer of Bulgarian Astronomy - Golev, V. (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 2008)
Some details of the early history and early timeline of modern Bulgarian astronomy are reviewed. The role of prof. Kiril Popov, member of Academy and a great Bulgarian mathemati